Census of population and housing : directory of census statistics. - Australian Bureau of Statistics ([Canberra] : Australian Bureau of Statistics, 1998)
Assists those interested in accessing information from the wealth of statistics collected in the Census of Population and Housing. The directory contains a description of the range of publications, electronic products, maps and consultancy services available from the 1996 Census. A brief description of the contents of each item is provided as well as details of the geographic coverage, price, availability by medium and ordering information.
Catalogue no. 2910.0.
"W. McLennan, Australian Statistician"--verso of cover.
"October 1998"--At foot of contents page.
Cover title.
"Census 1996"
Keywords: Censuses -- Australia; Australia -- Census, 1996 -- Catalogs